Tafsir Ayat-Ayat Puasa Dan Relevansinya Dalam Kehidupan Sosial - Rahmad Sahputra; Muhammad Riski; Sardiman Al-Fitra; Khoirul Azmi Harahap; Edi Hermanto (CV. ITTC INDONESIA, 2025)
Fasting is an act of worship in Islam that not only has a ritual dimension but also contains social values ​​relevant to community life. However, in practice, fasting is often understood narrowly as an act of abstaining from hunger and thirst, so its social values ​​are not fully realized in everyday life. This article aims to examine the interpretation of the verses on fasting in Surah Al-Baqarah, verses 183–187, and analyze their relevance to contemporary social life. This research uses a qualitative approach with library research through a review of the Quran, commentaries, and relevant literature. The results indicate that fasting, from a Quranic perspective, aims not only to foster individual piety but also social piety, reflected in empathy, solidarity, self-control, and concern for others. These values ​​have strong relevance in addressing the challenges of modern social life, so fasting needs to be understood and implemented more comprehensively as a means of moral and social development.